The expectations and realities of nutrigenomic testing in australia: A qualitative study - Erin Tutty; Chriselle Hickerton; Bronwyn Terrill; Belinda McClaren; Rigan Tytherleigh; Elaine Stackpoole; Jaqueline Savard; Ainsley Newson; Anna Middleton; Amy Nisselle; Marie Cusack; Melissa Adamski; et al. (Wiley, 2021)
Abstract Background Consumer genomic testing for nutrition and wellness, (nutritional genomics), is becoming increasingly popular. Concurrently, health‐care practitioners (HPs) working in private practice (including doctors interested in integrative medicine, private genetic counsellors, pharmacists, dieticians, naturopaths and nutritionists) are involved as test facilitators or interpreters. Objective To explore Australian consumers' and HPs' experiences with nutrigenomic testing. Method Semi‐structured in‐depth interviews were conducted using predominantly purposive sampling. The two data sets were analysed individually, then combined, using a constant comparative, thematic approach. Results Overall, 45 interviews were conducted with consumers (n = 18) and HPs (n = 27). Many of the consumer interviewees experienced chronic ill‐health. Nutrigenomic testing was perceived as empowering and a source of hope for answers. While most made changes to their diet/supplements post‐test, self‐reported health improvements were small. A positive relationship with their HP appeared to minimize disappointment. HPs' adoption and views of nutrigenomic testing varied. Those enthusiastic about testing saw the possibilities it could offer. However, many felt nutrigenomic testing was not the only 'tool' to utilize when offering health care. Discussion This research highlights the important role HPs play in consumers' experiences of nutrigenomics. The varied practice suggests relevant HPs require upskilling in this area to at least support their patients/clients, even if nutrigenomic testing is not part of their practice. Patient or public contribution Advisory group included patient/public group representatives who informed study design; focus group participants gave feedback on the survey from which consumer interviewees were sourced. This informed the HP data set design. Interviewees from HP data set assisted with snowball sampling.